Optical properties and electronic polarizability of boron-antimonide semiconductor - Daoud, Salah; Latreche, Abdelhakim (International Journal of Physical Research, 2017)
The high-frequency and static dielectric constants, the reflex index, the total optical electronegativity difference, the bulk modulus, the micro-hardness, the plasmon energy and the electronic polarizability of cubic zincblende boron-antimonide semiconductor have been estimated by using some empirical formulas. These parameters are analyzed by comparing them against the available experimental and theoretical data. In general, our obtained results agree well with other theoretical data from the literature.